The role of numerical and scientific literacy in preparing students for the challenges of the 21st century: A systematic review and bibliometrics analysis - Nalle, Christina; Ilma, Arina Zaida; Saryanto, Saryanto; Rejokirono, Rejokirono (Edelweiss Applied Science and Technology, 2025)
This study aims to identify research trends on the topic of numerical and scientific literacy. This study uses the Systematic Literature Review (SLR) and Bibliometric Analysis approaches. This review analyzes key themes, important concepts, and research gaps. Bibliometric analysis was conducted using software such as VOSviewer or RStudio. The findings reveal variations and fluctuations in the number of publications annually, with an increasing focus on scientific and numerical literacy as critical issues in both developed and developing countries. A thematic map highlights key research themes, particularly in scientific literacy, showcasing the diverse methodologies applied in this domain, including qualitative, review, mixed methods, quantitative, and research and development (R&D) approaches. The results underscore the importance of scientific understanding and numeracy skills in equipping individuals to navigate the complexities of scientific and numerical information. Additionally, the study emphasizes the integral role of instructional strategies, namely approach, model, method, assessment, and media. This research contributes to a deeper understanding of global trends and instructional practices in numerical and scientific literacy.